Into the universe of technical images - Flusser, Vilém, 1920-1991 (Electronic mediations, 2011)
Poised between hope and despair for a humanity facing an urgent communication crisis, this work by VilTm Flusser forecasts either the first truly human, infinitely creative society in history or a society of unbearable, oppressive sameness, locked in a pattern it cannot change. First published in German in 1985 and now available in English for the first time, Into the Universe of Technical Images outlines the history of communication technology as a process of increasing abstraction. Flusser charts how communication evolved from direct interaction with the world to mediation through various te.